Study of carbon nanotube forests based two degree of freedom angle sensor - Islam, Md.Saiful (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Angle sensor has been increasingly demanded by a big variety of applications spanning from angular position to speed detection. Commercially available angle sensors are typically based on capacitive, electrochemical and optical properties. These traditional angle sensors are large in size, complex detection method and have multiple complex fabrication techniques. Carbon nanotube (CNT) forests popularly known as vertically aligned carbon nanotube forests (VACNTs) have proven to be excellent candidates to meet this demand due to its unique electrical, mechanical and optical properties. Researchers have made an effort into developing different sensing applications using CNT forests. However, no research has been done yet to use optical properties of VACNTs to fabricate angle sensor. Tip bending process is implemented on the CNT forests. Interestingly, Tip bended CNT forests zone demonstrate significant optical reflection and also can be used for fabricating horizontally aligned carbon nanotube forests (HACNTs) mat. The circumferential surface of rotating tungsten roller is used to bend and align the individual nanotube in VACNTs array. Tip bending method using side surface of the tool was conducted using high precision micro-CNC machine, where all key parameters - rotational speed of the spindle, lateral speed of the tool in X-Y- direction, step size in Z-direction, total depth in Z-direction and surface roughness of the 500 μm diameter tool - were varied. . The process yielded remarkably arranged (horizontal) nanotubes with a resultant smooth surface. Different characterizations were conducted to investigate the results of tip bending (using circumferential surface of rotating tool) processed CNT forest sample using field emission scanning electron microscope (FESEM), energy-dispersive X-ray (EDS) spectroscopy, Atomic force microscopy(AFM) and optical microscopy. Depending on all the outcomes of the characterizations above, the best parameter was found to 2000 rpm (tool rotational speed), 1mm/min (lateral speed) and 1μm (step size) with best minimum surface roughness 4nm with 60 μm total depth. Furthermore, the tip bending process of CNT forests using the bottom surface of the rotating tungsten tool was studied and optimized to fabricate two degree of freedom (DOF) angle sensor. In this process, VACNTs were bent, densified and flattened by the bottom of the rotating tungsten tool. The patterned CNT forests area became optically reflective and used as a reflector in the angle sensor. The parameters were used to be 2000 rpm of tool rotational speed, 1mm/min lateral speed and 1μm step size. The patterned area was 5mm2 (1mm width and 5 mm length). Newly developed two DOF angle sensor was based on the combination of the single wavelength (partially polarized) laser beam, a linear polarizer, patterned VACNTs and two photodetectors for the rotational angle measurement. The patterned CNT forests were rotated from 100 to 300 and the polarizer was rotated from 00 to 3600. Finally, the prototype of the 2 DOF angle sensor was tested experimentally. The outcomes reveal that the sensor can measure the two directional angle in one sensor package. The sensitivity of the prototype at 100, 200 and 300 incident angle was 0.076 V/deg, 0.131 V/deg and 0.458 V/deg respectively.